Cost‐effectiveness of risk‐tailored screening strategy for colorectal cancer: A systematic review. Issue 7 (25th April 2022) - Wang, Le; Liu, Chengcheng; Wang, Youqing; Du, Lingbin
Abstract: Background and Aim: Though one‐size‐fits‐all age‐based screening for colorectal cancer (CRC) is effective in reducing the incidence and mortality, the evidence regarding on personized screening based on individual risk factors has been growing. The study aimed to perform a systematic review to synthesize economic evidence of risk‐tailored CRC screening strategies. Methods: This systematic review was conducted in EMBASE, Web of Science, PubMed, Cochrane Library, Econlit, and National Institute for Health Research Economic Evaluation Database from inception to June 30, 2021. We calculated the incremental cost‐effectiveness ratio (ICER) of cost per life year or quality‐adjusted life year gained for the risk‐tailored screening compared with no screening or uniform screening. A strategy was cost‐effective with less cost and equal or more effectiveness than the comparator along with lower ICER than the willingness‐to‐pay threshold. Results: Our review finally comprised seven studies. Five studies reported the results of comparisons of risk‐tailored CRC screening with no screening, and supported that risk‐tailored screening was cost‐effective. All of seven studies reported the ICERs of risk‐tailored screening and age‐based screening. Disparities in the discrimination of risk‐prediction tool, accuracy of adopted techniques, uptake rate of screening and cost estimation impacted the cost‐effectiveness. Conclusions: Studies on the economic evaluation of risk‐tailored CRC screening are limited, and current evidence is not sufficient to support the replacement of risk‐tailored screening for traditional age‐based screening.